Bodies that need queering: the queer hetero-topias in Malayalam cinema - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2023)
This edited volume offers a comprehensive understanding of the queer space in tandem with the transforming socio-cultural-political relationships in a country that exhibits diversified shades of ideologies and history – that is, India. The featured essays deal with the presence of queerness in visual media, particularly in films and the digital arena, from multilingual and multicultural perspectives, thus creating an exhaustive discourse encompassing argument and analysis. This book aims to depict the plurality and complexity of the Indian scenario, fostering mass acceptance of queerness, a rare scholastic endeavour.
Keywords: LGBTQ+ films; Malayalam cinema